Efficiency of Baitul Maal wa Tamwil (BMT) as Islamic Microfinance Institution in Indonesia: An Application of Data Envelopment Analysis - Atiqi Chollisni Nasution (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2013)
The primary objectives of most microfinance program isalleviating the poverty by assisting the poor to be economicallyindependent. Different with conventional microfinance that offersthe financing scheme based on interest (read: riba), Islamicmicrofinance offers the financing scheme based on shariahprinciples to enhance the business development ofmicroentrepreneurs. Furthermore, Islamic microfinance assiststhe microentrepreneurs to applicate the Islamic ethics in dailylife that effects to press the number default of payment. Recently,there are around 4,000 Baitul Maal Wa Tamwil (BMTs) operateand have enhanced thousand poor people life in Indonesia. Theyare Islamic Microfinance Institutions (Islamic MFIs) thatresponsible in collecting, managing and distributing the fundseither for charity (e.g for the poorest) or providing financialservices for the microentrepreneurs. In addition, measuringefficiency of microfinance program is important to enable themicrofinance institutions (MFIs) to strengthen the management,generate sufficient profits and maintain efficient operations toensure its sustainability. The main aim of the paper is to examinethe efficiency of BMTs as Islamic microfinance institutions inIndonesia. Data Envelopment Analysis (DEA) is used to examinethe relative efficiency of the selected BMTs. DEA is a nonparametric method which utilize the linear programming methodto measure technical (technological) efficiency and requiresinputs and outputs data. Twelve large size BMTs are chosen as18ISLAMINOMIC JURNAL Jurnal Ekonomi dan Perbankan Syariahthe sample of the study and they have operated in the provincesof Indonesia with the highest number of poor people live. Thestudy indicated that financing and human resources are the basesof inefficiency in BMTs. Inefficient BMTs are expected tooptimize its operations by emulating the input minimization andoutput maximization practices adopted by efficient BMTs. Thefindings are not only relevant and applicable to Indonesia butalso to other muslim countries and would be useful for furtherempirical research in this area.